Social Security Protection for Seafarers (Internatinal Labour Office, 1986)
International labour conference 74th(maritime) session 1987 report iii (1). Social security protection for seafarers including those serving in ships flying flags other than those of their own country.
Keywords: Social security-Seafarers-ILO collection-Nonfiction